2022
DOI: 10.3389/fenrg.2022.951235
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Country Risks on the Dependence Patterns of International Cobalt Trade: A Network Analysis Method

Abstract: Cobalt is a key resource for the global energy transition, and the differences in the natural endowment of cobalt have led to frequent cobalt trade among countries. This study aims to reveal the dependence patterns of cobalt trade among countries and the impact of country risks (including political and economic risks) on the patterns. First, a cobalt import dependence network (CIDN) and a cobalt export dependence network (CEDN) are established using the network analysis method. Furthermore, this study uses net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…The country risk (LogRISK) showed a reduction of country costs at 1%, promoting the performance of the Portuguese export in (0.693%) and (0.911%) with OLS and the random effect estimator, respectively. Previous studies by Shi et al (2022), Wang et al (2021), Hassan (2022), and Goswami and Panthamit (2022) also found similar results.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…The country risk (LogRISK) showed a reduction of country costs at 1%, promoting the performance of the Portuguese export in (0.693%) and (0.911%) with OLS and the random effect estimator, respectively. Previous studies by Shi et al (2022), Wang et al (2021), Hassan (2022), and Goswami and Panthamit (2022) also found similar results.…”
Section: Resultssupporting
confidence: 79%
“…Several articles about the gravity model, such as those by Moser et al (2008), Gupta et al (2019), Wang et al (2021), andShi et al (2022), studied the impact of country risk on trade flows. The literature on international economics states that the country's risk of an economy can affect the flows of international trade and investment, particularly if this economy has a high country risk.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations